New Research Directions in DNA Repair - Chen, Clark (IntechOpen, 2013)
This book is intended for students and scientists working in the field of DNA repair. Select topics are presented here to illustrate novel concepts in DNA repair, the cross-talks between DNA repair and other fundamental cellular processes, and clinical translational efforts based on paradigms established in DNA repair. The book should serve as a supplementary text in courses and seminars as well as a general reference for biologists with an interest in DNA repair.